Assessment of the Myogenic and Metabolic Mechanism Influence in Cerebral Autoregulation Using Near-Infrared Spectroscopy (2011)
Cerebral autoregulation is normally controlled via three different mechanisms, namely: the myogenic, the metabolic, and the neurogenic one. The myogenic mechanism responds efficiently to slow changes in mean arterial blood pressure (MABP) while the metabolic one is more efficient with fast changes. The neurogenic mechanism is not yet well understood. As changes in cerebral intravascular oxygenation (HbD), measured with near-infrared spectroscopy (NIRS), reflect changes in cerebral blood flow, the myogenic influence in the cerebral autoregulation can be assessed by analysis of HbD and MABP; the metabolic influence can be assessed by analysis of the HbD and the partial pressure of carbon dioxide (pCO2). We performed a transfer function analysis in order to calculate the gain and phase of the HbD/MABP and HbD/PCO2 subsystems. Due to the fact that cerebral autoregulation may be absent in sick premature infants, we then investigated how well these parameters could predict clinical outcome in this population.